Facebook Online Support Groups for Hospice Family Caregivers of Advanced Cancer Patients: Protocol, Facilitation Skills and Promising Outcomes. Issue 2 (3rd April 2022) - Parker Oliver, Debra; Washington, Karla T.; Benson, Jacquelyn; White, Patrick; Cruz Oliver, Dulce; Smith, Jamie B; Mazur, Joshua; Lakew, Abeba; Lewis, Alexandra; Demiris, George
Abstract: Research has demonstrated a lack of support for hospice caregivers and a higher than average level of self-reported anxiety and depression. While online support groups are gaining popularity, few protocols have been published, little research has demonstrated the skills required to facilitate, and virtually no data has explored the clinical outcomes affiliated with participation in such groups. This paper presents the preliminary experience and results of a clinical trial testing the use of online support groups designed to both educate and provide social support to caregivers of hospice cancer patients. A detailed protocol outlines educational strategies, discussion questions, and a blueprint outlining ways to engage participants. A review of field notes completed by the interventionist reveal specific facilitation skills and strategies used to engage participants. Finally, preliminary analysis of 78 participants shows the group is having a statistically significant impact on the caregiver depression.